2011
DOI: 10.4254/wjh.v3.i1.24
|View full text |Cite
|
Sign up to set email alerts
|

First multicenter study for risk factors for hepatocellular carcinoma development in North Africa

Abstract: HCV and HBV infections and diabetes are the main determinants of HCC development in North Africa. An active surveillance and secondary prevention programs for patients with chronic hepatitis and nutrition-associated metabolic liver diseases are the most important steps to reduce the risk of HCC in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Our finding are also in accordance with some studies conducted in West Africa countries like Nigeria [27], Gambia [28] and Ghana [29]. Our results contrast however, with those of North Africa HCC patient [23]. It seems thus, that the kinetics of tumor development is stable since decades and homogeneous throughout Sub Saharan Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding are also in accordance with some studies conducted in West Africa countries like Nigeria [27], Gambia [28] and Ghana [29]. Our results contrast however, with those of North Africa HCC patient [23]. It seems thus, that the kinetics of tumor development is stable since decades and homogeneous throughout Sub Saharan Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Alcohol played a minor role as a risk factor for HCC (76-78). Another study about HCC development in North Africa in 2011 revealed that 60% of HCC patients in the study were infected with HCV and only 17.9% with HBV (79). These results were different from that were reported by another group in North Africa in the 1990s in which the authors revealed that HBV prevalence among HCC patients was 60% (80).…”
Section: Evidence Acquisitionmentioning
confidence: 96%
“…There were not so many studies on risk difference in HCV genotypes in general population. Some studies, including prospective cohort and meta-analysis, have suggested that HCV genotype 1b plays the most important role in HCC development [8,10,11] but most studies included in the meta-analysis were based on patients with chronic hepatitis or liver cirrhosis [8]. …”
Section: Introductionmentioning
confidence: 99%